BDNF and JNK Signaling Modulate Cortical Interneuron and Perineuronal Net Development: Implications for Schizophrenia-Linked 16p11.2 Duplication Syndrome. (17th October 2020) - Willis, Ashleigh; Pratt, Judith A; Morris, Brian J
Abstract: Schizophrenia (SZ) is a neurodevelopmental disorder caused by the interaction of genetic and environmental risk factors. One of the strongest genetic risk variants is duplication (DUP) of chr.16p11.2. SZ is characterized by cortical gamma-amino-butyric acid (GABA)ergic interneuron dysfunction and disruption to surrounding extracellular matrix structures, perineuronal nets (PNNs). Developmental maturation of GABAergic interneurons, and also the resulting closure of the critical period of cortical plasticity, is regulated by brain-derived neurotrophic factor (BDNF), although the mechanisms involved are unknown. Here, we show that BDNF promotes GABAergic interneuron and PNN maturation through JNK signaling. In mice reproducing the 16p11.2 DUP, where the JNK upstream activator Taok2 is overexpressed, we find that JNK is overactive and there are developmental abnormalities in PNNs, which persist into adulthood. Prefrontal cortex parvalbumin (PVB) expression is reduced, while PNN intensity is increased. Additionally, we report a unique role for TAOK2 signaling in the regulation of PVB interneurons. Our work implicates TAOK2-JNK signaling in cortical interneuron and PNN development, and in the responses to BDNF. It also demonstrates that over-activation of this pathway in conditions associated with SZ risk causes long-lasting disruption in cortical interneurons.